Cochlear Implantation in Children with Inner Ear Malformation and Cochlear Nerve Deficiency - Kaga, Kimitaka (Springer Singapore : Imprint: Springer, 2017)
The purpose of this book is to contribute to basic and clinical medical research on cochlear implants for inner ear malformation and cochlear nerve deficiency. Cochlear implantation for children is performed worldwide, and the outcomes concerning speech and hearing acquisition are epoch-making. However, there are some difficulties associated with applying this operative treatment to patients who have complicated inner ear malformations or cochlear nerve deficiencies that have slowed the development of their speech, hearing, and/or sense of balance. The first part of the book outlines the fundamental aspects of inner ear maldevelopment to facilitate readers' understanding of cochlear implantation from the point of view of embryology, morphology, and genetics. In turn, the second part describes current clinical cases and presents successful clinical reports. The book offers a primary resource for otolaryngologists, neurologists, and pediatricians with an interest in this field.
Keywords: Medicine.; Neurology.; Otorhinolaryngology.; Pediatric surgery.; elektronické knihy; electronic books